Diseminasi Online Multimedia Pembelajaran Matematika yang Dikembangkan Menggunakan Videoscribe - Puji Astuti; Febrian Febrian (Fakultas Keguruan dan Ilmu Pendidikan Universitas Maritim Raja Ali Haji, 2019)
In the industrial revolution 4.0 era, teacher needs to utilize information and communication technology (ICT) in learning. The professionalism competencies proclaimed by teachers also require teachers to be able to develop interactive and interesting learning media so that there is an increase in the quality of learning. This challenge is inversely proportional to the conditions in the field, namely that there are no teachers in the Mathematics Teacher Association(MGMP) at SMA and SMK in Bintan Regency who develop learning multimedia and utilize technology such as social media as learning media. For this reason, Community Service (PkM) activities needs to be conducted, with theme disseminating learning multimedia with videoscribe on social media (e-learning). The PkM activity was concluded to be going well with indicator 1) 100% participant (teacher) got involved during mentoring; 2) the production of learning video by teachers and the dissemination of the learning videos on the YouTube channel; 3) teacher participants require for more training activities.